Investigating the influence of monetary policy on the balance sheet performance of commercial banks - Kalua, Denis; Lipunga, Andrew Munthopa; Banda, Fredrick (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: The study investigates the influence of monetary policy on the balance sheet performance of commercial banks in Malawi.Design/Methodology/Approach: The study employed an explanatory research design using time series data obtained from financial reports of commercial banks and economic reports published by the Reserve Bank of Malawi from 2012 to 2022. Regression analyses were conducted to establish the influence of monetary policy on balance sheet performance (loan and overdraft growth).Research findings: The results suggest that the monetary policy instruments, namely, the liquidity reserve requirement (LRR), Lombard rate, policy rate, and open market operations, have insignificant influence on the loan and overdraft growth in commercial banks in Malawi.Theoretical contribution/Originality: This implies that these monetary policy tools are not the exterior determinants of the balance sheet performance of commercial banks in Malawi.Research limitation: The study used a single measure of the balance sheet performance of commercial banks.